2018
DOI: 10.12783/dtcse/csae2017/17552
|View full text |Cite
|
Sign up to set email alerts
|

Using Convolutional Layer Features for Indoor Human Activity Recognition based on Spatial Location Information

Abstract: Identifying human actions has great importance for various applications, especially in the smart home, fitness tracking and health monitoring domains. However, human activity recognition still remains a challenging task. This is mainly due to the broad range of human activities as well as the rich variation of a given activity can be performed. In this paper, we dealt with the problem by making use of spatial location information of three different parts of a human body, which are derived via three UWB (ultraw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The methods in natural scenes cannot be used directly due to the abundant texture and shape features. Li J. et al [15] found that CNNs can implicitly learn spatial location information. The CNN learns the characteristic information of the primitives, and uses this characteristic information to segment the periodic pattern primitives of the printed fabric.…”
Section: Introductionmentioning
confidence: 99%
“…The methods in natural scenes cannot be used directly due to the abundant texture and shape features. Li J. et al [15] found that CNNs can implicitly learn spatial location information. The CNN learns the characteristic information of the primitives, and uses this characteristic information to segment the periodic pattern primitives of the printed fabric.…”
Section: Introductionmentioning
confidence: 99%